Healthcare redesign: meaning, origins and application. Issue 1 (1st February 2003) - Locock, L
Abstract : Healthcare organisations are using redesign to tackle variation in the quality of care and improve public satisfaction. It is represented as a radical challenge to traditional assumptions and practices which involves thinking through the best process to achieve speedy and effective patient care, identifying delays, unnecessary steps, or potential for error, and redesigning the process to improve the quality of care. This paper explores the meaning of redesign using practical illustrations. It examines its theoretical origins, particularly total quality management (TQM)/continuous quality improvement (CQI) and re-engineering, and assesses evidence which may inform its application. This evidence suggests that clinical ownership and senior management support will be essential. Redesign seeks to balance the more gradual approach of TQM with the organisation-wide lateral thinking of re-engineering. An incremental negotiated approach seems more likely to ensure clinical ownership, but carries a risk that QI will remain small scale with little impact on the wider organisation. Inclusion of some re-engineering techniques may help to overcome this difficulty. Evidence suggests that most QI techniques achieve only partial success. This may pose difficulties for redesign, which has generated high political expectations that it can solve long term problems in health care.